A behavioral approach to asset pricing - Shefrin, Hersh, 1948- (Amsterdam ; Boston : Academic Press/Elsevier, 2008)
Behavioral finance is the study of how psychology affects financial decision making and financial markets. It is increasingly becoming the common way of understanding investor behavior and stock market activity. In this 2nd Edition Hersh Shefrin examines the reigning assumptions of asset pricing theory and reconstructs them to incorporate findings from behavioral finance. In other words, he takes the traditional tools in asset pricing and behavioralizes them. He constructs a solid, intact structure that challenges classic assumptions and at the same time provides a strong theory and efficient empirical tools. Building on the models developed by both traditional asset pricing theorists and behavioral asset pricing theorists, Shefrin's book takes the discussion to the next step. He provides a general behaviorally based intertemporal treatment of asset pricing theory that extends to the discussion of derivatives, fixed income securities, mean-variance efficient portfolios, and the market portfolio, based on all the latest research and theory. * The second edition continues the tradition of the first edition by being the one and only book to focus completely on how behavioral finance principles affect asset pricing, now with its theory deepened and enriched by a plethora of research since the first edition * A companion website contains a series of examples worked out as Excel spreadsheets so that readers can input their own data to test the results.
Preface -- Preface to the Second Edition -- Introduction -- I Heuristics and Representativeness: Experimental Evidence -- Representativeness and Bayes Rule: Psychological Perspective -- Representativeness and Bayes Rule: Economics Perspective -- A Simple Asset Pricing Model Featuring Representativeness -- Heterogeneous Judgements in Experiments -- II Heuristics and Representativeness: Investor Expectations -- Representativeness and Heterogeneous Beliefs Among Individual Investors, Financial Executives, and Academics -- Representativeness and Heterogeneity in the Judgements of Professional Investors -- III Developing Behavioral Asset Pricing Models -- A Simple Asset Pricing Model with Heterogeneous Beliefs -- Heterogeneous Beliefs and Inefficient Markets -- A Simple Market Model of Prices and Trading Volume -- Efficiency and Entropy: Long-run Dynamics -- IV Heterogeneity in Risk Tolerance and Time Discounting -- CRRA and CARA Utility Functions -- Heterogeneous Risk Tolerance and Time Preference -- Representative Investors in a Heterogeneous CRRA Model -- IV Sentiment and Behavioral SDF -- Sentiment -- Behavioral SDF and the Sentiment Premium -- VI Applications and Behavioral SDF -- Behavioral Betas and Mean-Variance Portfolios -- Cross-section of Return Expectations -- Testing for a Sentiment Premium -- A Behavioral Approach to the Term Structure of Interest Rates -- Behavioral Black-Scholes -- Irrational Exuberance and Option Smiles -- Empirical Evidence in Support of Behavioral SDF -- VII Prospect Theory -- Prospect Theory: Introduction -- Behavioral Portfolios -- Equilibrium with Behavioral Preferences -- Pricing and Prospect Theory: Empirical Studies -- Reflections on the Equity Premium Puzzle -- Continuous Time Behavioral Equilibrium Models -- Conclusion -- References.
Includes bibliographical references (pages [563]-586) and index.
Keywords: Capital assets pricing model; Risk management